Investor-State Dispute Settlement Reform: Reconsidering the Multilateral Investment Court in the Context of Disputes Involving Intellectual Property Law - Zhao, Mary (The Columbia Journal of Law & the Arts, 2021)
On January 18, 2019, the European Commission submitted a proposal to the United Nations Commission on International Trade Law to establish a multilateral investment court for investor-state disputes. The European Commission’s proposal reflects growing discussions about the potential reform of the investor-state dispute settlement system. While the present work on reform options focuses on issues relating to the legitimacy of the investor-state dispute settlement system, the effects of the reform options on investor-state disputes that specifically involve intellectual property law remain to be examined. This Article argues that although the proposed multilateral court structure offers a comprehensive approach to addressing the concerns with the investor-state dispute settlement system, it does not address a number of issues that are specific to disputes involving intellectual property law. This Article analyzes issues that arise from the arbitral tribunal’s role in investor-state disputes that involve laws governing intellectual property at the international and domestic levels. In doing so, this Article shows that these issues are distinct from the ones that broadly relate to the legitimacy of the investor-state dispute settlement system. In light of these issues, this Article proposes additional considerations for the multilateral investment court structure. Specifically, this Article proposes including expertise in the relevant international agreements as a selection criteria for adjudicators and giving deference to the host state’s courts in disputes that involve issues of domestic intellectual property law.